2004
DOI: 10.14411/fp.2004.017
|View full text |Cite
|
Sign up to set email alerts
|

A review of Dendromonocotyle (Monogenea: Monocotylidae) from the skin of stingrays and their control in public aquaria

Abstract: Abstract. Dendromonocotyle species (Monogenea: Monocotylidae) are the only monocotylids to parasitize the skin of chondrichthyan hosts. Currently 11 species are recorded from the skin of ray species in the Dasyatidae, Myliobatidae and Urolophidae. There have been increasing reports of Dendromonocotyle outbreaks on rays kept in public aquaria. This paper provides a broad review of Dendromonocotyle that should assist taxonomists and aquarists with species identification and help decisions on potential control me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Until now, oral application at this dosage in elasmobranchs has not been investigated. Janse and Borgsteede (2003) presented results of both a bath treatment and oral application of praziquantel to treat captive spotted eagle rays Aetobatus narinari (Euphrasen, 1790) infected with monocotylids they misidentified as Clemacotyle australis Young, 1967 (likely Dendromonocotyle torosa Chisholm et Whittington, 2004;see Whittington and Chisholm 2008) and an unidentified hexabothriid species. Orally administered praziquantel at 10-40 mg/kg (note the exact concentrations are difficult to interpret from their results) did not remove the parasites infecting A. narinari, but limited shortterm success was achieved with bath treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, oral application at this dosage in elasmobranchs has not been investigated. Janse and Borgsteede (2003) presented results of both a bath treatment and oral application of praziquantel to treat captive spotted eagle rays Aetobatus narinari (Euphrasen, 1790) infected with monocotylids they misidentified as Clemacotyle australis Young, 1967 (likely Dendromonocotyle torosa Chisholm et Whittington, 2004;see Whittington and Chisholm 2008) and an unidentified hexabothriid species. Orally administered praziquantel at 10-40 mg/kg (note the exact concentrations are difficult to interpret from their results) did not remove the parasites infecting A. narinari, but limited shortterm success was achieved with bath treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Monocotylid monogeneans are known to cause health problems in stingrays maintained in public aquaria (Chisholm and Whittington 2002, Janse and Borgsteede 2003, Chisholm et al 2004, Vaughan et al 2008a, Vaughan and Chisholm 2009). Monocotylids parasitising the skin surface of stingrays held in captivity have received the most attention because infections are more visible and physical damage associated with feeding worms typically presents itself as conspicuous tissue discolouration.…”
Section: Introductionmentioning
confidence: 99%
“…This is the fi rst record of D. kuhlii from a public aquarium. Chisholm et al (2004) found that a proactive approach to their management, by reducing host stress, supported a sustainable equilibrium between host and parasite. Identifying and reducing stressors is paramount, but not always possible.…”
Section: S I T E O N H O S T : Dorsal Skin Surface M a T E R I A L Dmentioning
confidence: 96%
“…There are currently 16 known species of Dendromonocotyle, of which 7 are reported from stingrays in captivity (see Chisholm and Whittington 1995, 2009, Chisholm et al 2001, 2004, Vaughan et al 2008. It has become clear that Dendromonocotyle infections can cause health problems in stingrays kept in public aquaria.…”
Section: Members Of Dendromonocotylementioning
confidence: 99%
“…Members of Dendromonocotyle (Monogenea, Monocotylidae) parasitise the dorsal surface of stingrays and have been recorded from ray species in the Dasyatidae, Myliobatidae and Urolophidae (see Chisholm et al 2004). The porcupine ray, Urogymnus asperrimus (Bloch et Schneider, 1801) has a wide distribution throughout the Indian and Indo-West Pacific Oceans but is rarely collected in the coastal waters of Australia (Last and Stevens 1994, Theiss et al in press).…”
Section: Introductionmentioning
confidence: 99%